Estudo das relações filogenéticas em Satanoperca Günther, 1862 (Perciformes: Cichlidae). - Deprá, Gabriel de Carvalho (2014)
A hypothesis of the phylogenetic relationships among the species in Satanoperca is presented, based in 121 morphological characters, several described for the first time. Thirty-three terminal taxa were used, seven of which are valid species in Satanoperca (only S. rhynchitis was not included) and four are putatively new species of Satanoperca. From 24 out-group taxa, 14 belong in Geophaginae, subfamily including Satanoperca. The maximum parsimony analysis resulted in one most-parsimonious cladogram, with CI = 0.399 and RI = 0.608. Monophyly of Satanoperca was strongly supported (bootstrap = 100), with 21 synapomorphies, six of which exclusive (among these, five described for the first time). Monophyly of S. daemon and S. jurupari species groups was corroborated. The S. acuticeps species group was found as sister to the S. daemon species group, and this clade as sister to the S. jurupari species group, in which all of the new species were found. Internal relationships of this group were almost fully resolved. Species presenting white spots on the face (S. leucosticta, S. mapiritensis and Satanoperca sp. 2) were found to form a monophyletic group. Another monophyletic group includes S. pappaterra, Satanoperca sp. 1 and Satanoperca sp. Xingu , species which have a more extensive squamation on the caudal fin. Differences in supra-cleithrum and post-temporal shape between S. jurupari and S. mapiritensis corroborate validity of the latter, which has been considered by other authors as a junior synonym to S. jurupari.